Validity of a 6-item movement control test battery for evaluation of movement control impairment in the lumbar spine. - Peemongkon Wattananon; Aminu Alhassan Ibrahim; Sasithorn Kongoun; Katayan Klahan (PLoS ONE)
Background Patients with chronic non-specific low back pain (CNLBP) demonstrate movement control impairment (MCI) based on a 6-item motor control test (MCT) battery, suggesting its potential clinical utility. Objectives This study aimed to determine the criterion-related validity of the 6-item MCT battery in discriminating MCI among individuals with CNLBP, a history of low back pain (HxLBP), and no low back pain (NoLBP). Methods One hundred forty-one participants aged 20-40 years (47 participants per group) were recruited. The MCT battery (the waiter's bow, pelvic tilt, sitting knee extension, quadruped rocking forward, quadruped rocking backward, prone knee flexion) was rated using different rating methods, including individual tests, summation, and direction-specific tests. A 2x2 contingency table using a known group against the rating result was used to calculate chi-square, sensitivity, specificity, and positive and negative likelihood ratios for each pair separately. Results Chi-square tests demonstrated significant associations (P < 0.05) between MCT and CNLBP when compared against NoLBP. In addition, the waiter's bow and flexion-specific tests demonstrated high sensitivity (81% and 72%, respectively), while sitting knee extension, prone knee flexion, and summation demonstrated high specificity (70%, 70%, and 89%, respectively). Conclusion Findings suggest the acceptable validity of the MCT battery when compared between CNLBP and NoLBP. The waiter's bow and flexion-specific tests effectively ruled out individuals with NoLBP with negative results, while sitting knee extension, prone knee flexion, and summation effectively ruled in the individuals with CNLBP with positive results. These findings highlight the clinical utility of these tests in assessing MCI in the lumbar spine.